2009
DOI: 10.1164/rccm.200807-1043oc
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Ambient Ultrafine Particle Exposure Induces Cardiac Changes in Young Healthy Volunteers

Abstract: These findings show mild inflammatory and prothrombic responses and are suggestive of alterations in cardiac repolarization induced by UFCAP inhalation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
102
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 62 publications
14
102
2
1
Order By: Relevance
“…At 24 hours post-inhalation, endothelium-dependent vasodilatation (induced by acetylcholine and bradykinin) remained impaired, while endothelium-independent vasodilatation (using sodium nitroprusside and verapamil) and t-PA release were unaffected, in the presence of mild sytemic inflammation ). These and other (Bonzini et al 2010, Chuang et al 2007, Ghio et al 2003, Samet et al 2009) studies did not demonstrate an assocation between PM exposure and baseline levels (not bradykinin-induced) of t-PA. While studies, based on controlled exposure to diluted diesel exhaust , Carlsten et al 2007 or concentrated ambient particles (Ghio et al 2003), did not observe increases in the levels of plasminogen activator inhibitor-1 (PAI-1), some epidemiological or animal studies, focussing on urban PM, did: a study in 76 young healthy students demonstrated elevated PAI-1 concentrations in association with the mean PM 2.5 or PM 10 concentration at their university's campus over 1 to 3 days (Chuang et al 2007).…”
Section: Endothelial Function and Fibrinolysismentioning
confidence: 41%
“…At 24 hours post-inhalation, endothelium-dependent vasodilatation (induced by acetylcholine and bradykinin) remained impaired, while endothelium-independent vasodilatation (using sodium nitroprusside and verapamil) and t-PA release were unaffected, in the presence of mild sytemic inflammation ). These and other (Bonzini et al 2010, Chuang et al 2007, Ghio et al 2003, Samet et al 2009) studies did not demonstrate an assocation between PM exposure and baseline levels (not bradykinin-induced) of t-PA. While studies, based on controlled exposure to diluted diesel exhaust , Carlsten et al 2007 or concentrated ambient particles (Ghio et al 2003), did not observe increases in the levels of plasminogen activator inhibitor-1 (PAI-1), some epidemiological or animal studies, focussing on urban PM, did: a study in 76 young healthy students demonstrated elevated PAI-1 concentrations in association with the mean PM 2.5 or PM 10 concentration at their university's campus over 1 to 3 days (Chuang et al 2007).…”
Section: Endothelial Function and Fibrinolysismentioning
confidence: 41%
“…We have previously reported that activation of fibrinolysis pathways and increased levels of D-dimer (a fibrin breakdown product) are associated with exposure to PM air pollution in humans. 28 We also show that ozone can mirror the established effects of PM and cause changes in HRV and cardiac repolarization. We observed a decrease in the HF component of HRV immediately after ozone exposure, which is consistent with findings in multiple PM studies (PM Integrated Science Assessment).…”
Section: Discussionmentioning
confidence: 53%
“…Chalk PM 2.5 could also stimulate alveolar macrophages to produce reactive oxygen species and cause oxidative stress and cytotoxicity (Zhang et al, 2015a, b). Although the adverse health effects of ultrafine particles remains uncertain, various experimental studies have indicated that human exposure to nanoparticles is related to cardiovascular diseases (Lucking et al, 2008;Langrish et al, 2009;Samet et al, 2009). According to Figs.…”
Section: Particle Size Distribution Of Chalk Dustmentioning
confidence: 99%